STRUGGLE FOR LIFE OF MITCH IN THE FIRM MOVIE:AN INDIVIDUAL PSYCHOLOGICAL APPROACH - PURNAMI, INDAH (2007)
The problem of this study is how the struggle for life influences Mitch's personality viewed from individual psychology, and to analyze the movie based on its structural elements. The research is conducted by using qualitative method. In this method, the research uses two data sources, namely primary and secondary data sources. The primary data is The Firm directed by Sydney Pollack. The secondary data sources are gained from the author's biography, essay, comment, historical information, the other books, and thesis that are related to the research. Technique of the data collections is library research. Based on the analysis, the writer draws some conclusions as follows: the personality of Mitch is changing because of his struggle to make his life better and his brother Ray out of jail. Mitch must work hard in Bendini, Lambert, and Locke a law firm to get his goal come true.